(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The equations of state (EOS) and other thermodynamic properties of hcp structure Zr_2Al are studied using first-principles calculations based on the plane wave pseudopotential density functional theory method within the generalized gradient approximation (GGA) for exchange and correlation. It is demonstrated that the ratio c/a of about 1.208 is the most stable structure for the hcp Zr_2Al, which is consistent with the experimental data. Through the quasi-harmonic Debye model, in which the phononic effects are considered, the dependences of relative volume V/V_0 on pressure P, cell volume V on temperature T are successfully obtained. The variations of the Debye temperature Θ, the thermal expansion a , the Grüneisen parameter γ and the heat capacity C_v with pressure P and temperature T are investigated systematically in the ranges of 0-100 GPa and 0-1500 K.